2014
DOI: 10.1186/1471-2407-14-558
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the interval cancer rate and its determinants on the Girona health region’s early breast cancer detection program

Abstract: BackgroundThe main aim of this study is to estimate the rate of false negative and true IC on the Program for the Early Detection of Breast Cancer (PEDBC) run by the Girona Health Region (GHR) and compare the clinicopathological characteristics of these tumors with those detected within the same program.MethodsA retrospective cohort study including all women participating on the Girona PEDBC between 2000 and 2006, with negative mammography screening. The IC included are those detected between the first and sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…Among true interval BCs, triple-negative tumours were more frequently observed in fatty (<25% density) than in denser breasts ( p <0.001). FNs and occult interval BCs had similar phenotypic characteristics to screen-detected cancers.Renart-Vicens 26 Interval vs. screen-detected BCs from Girona Health Region screening program 2000–06.Interval BCs had significantly higher proportions of advanced stage disease (14% vs. 1%), larger tumours (5.4% vs. 2.3%), high-grade tumours (38% vs. 23%), and higher number of metastatic nodes (13.5% vs. 7.7%) than screen-detected BCs.Interval BCs were non-significantly more likely to be triple-negative, and less likely to be luminal A tumours than screen-detected BCs.Boyd 11 Interval vs. screen-detected BCs sourced from three case–control studies nested in screened populations, by density measured with various methods.Interval BCs had significantly larger (average) maximum tumour diameter for each measure of density (percent mammographic density, dense and non-dense areas) than screen-detected BCs.Caldarella 43 Interval vs. screen-detected BCs, Florence population screening program 2004–05.Stage at diagnosis was more advanced for interval BCs than screen-detected BCs based on pT distribution (pT 2+ 25.8% vs. 10.4%, p  < 0.001) and pN distribution (pN 1+ 41% vs. 29%, p  = 0.032).Relative to screen-detected BC, triple-negative BCs were over-represented, and luminal A (ER/PR positive, HER2 negative) BCs were under-represented among interval BCsPayne 39 Interval vs. screen-detected BCs from Nova Scotia screening program 1991–2004.Interval BCs were more likely to be node-positive, to be larger tumours, to have higher grade, and to show lymphovascular invasion than screen-detected BCs (all p  < 0.001).Interval BCs less likely to be ER positive than screen-detected BCs ( p  = 0.002).Kalager 46 Interval BC in the Norwegian screening program vs. BCs in same time frame in population not yet invited to screening (non-screened women).Interval BCs had slightly higher proportions of larger tumours (>20 mm), stage II rather than stage I cancer, invasive lobular histology, and negative (non-metastatic) axillary nodes, than BCs in non-screened women (distributions for these variables differed at p  < 0.001).Caumo 44 Interval vs. screen-detected vs. clinical BCs occurring in the absence of screening, Verona mammography screening program 2000–06 and Veneto cancer registry.Interval BCs had more aggressive features than screen-detected BCs for pT ( p  < 0.001), pN ( p  < 0.001), and tumour grade distributions ( p  =  0.007). Interval BCs had similar prognostic features as clinical BCs based on pT, pN and grade distributions (all p  > 0.05).Interval BCs less likely to be ER-positive (77% vs. 91%, p  < 0.001) and PR-positive (61% vs. 82%, p  < 0.001) than screen-detected BCs.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…Among true interval BCs, triple-negative tumours were more frequently observed in fatty (<25% density) than in denser breasts ( p <0.001). FNs and occult interval BCs had similar phenotypic characteristics to screen-detected cancers.Renart-Vicens 26 Interval vs. screen-detected BCs from Girona Health Region screening program 2000–06.Interval BCs had significantly higher proportions of advanced stage disease (14% vs. 1%), larger tumours (5.4% vs. 2.3%), high-grade tumours (38% vs. 23%), and higher number of metastatic nodes (13.5% vs. 7.7%) than screen-detected BCs.Interval BCs were non-significantly more likely to be triple-negative, and less likely to be luminal A tumours than screen-detected BCs.Boyd 11 Interval vs. screen-detected BCs sourced from three case–control studies nested in screened populations, by density measured with various methods.Interval BCs had significantly larger (average) maximum tumour diameter for each measure of density (percent mammographic density, dense and non-dense areas) than screen-detected BCs.Caldarella 43 Interval vs. screen-detected BCs, Florence population screening program 2004–05.Stage at diagnosis was more advanced for interval BCs than screen-detected BCs based on pT distribution (pT 2+ 25.8% vs. 10.4%, p  < 0.001) and pN distribution (pN 1+ 41% vs. 29%, p  = 0.032).Relative to screen-detected BC, triple-negative BCs were over-represented, and luminal A (ER/PR positive, HER2 negative) BCs were under-represented among interval BCsPayne 39 Interval vs. screen-detected BCs from Nova Scotia screening program 1991–2004.Interval BCs were more likely to be node-positive, to be larger tumours, to have higher grade, and to show lymphovascular invasion than screen-detected BCs (all p  < 0.001).Interval BCs less likely to be ER positive than screen-detected BCs ( p  = 0.002).Kalager 46 Interval BC in the Norwegian screening program vs. BCs in same time frame in population not yet invited to screening (non-screened women).Interval BCs had slightly higher proportions of larger tumours (>20 mm), stage II rather than stage I cancer, invasive lobular histology, and negative (non-metastatic) axillary nodes, than BCs in non-screened women (distributions for these variables differed at p  < 0.001).Caumo 44 Interval vs. screen-detected vs. clinical BCs occurring in the absence of screening, Verona mammography screening program 2000–06 and Veneto cancer registry.Interval BCs had more aggressive features than screen-detected BCs for pT ( p  < 0.001), pN ( p  < 0.001), and tumour grade distributions ( p  =  0.007). Interval BCs had similar prognostic features as clinical BCs based on pT, pN and grade distributions (all p  > 0.05).Interval BCs less likely to be ER-positive (77% vs. 91%, p  < 0.001) and PR-positive (61% vs. 82%, p  < 0.001) than screen-detected BCs.…”
Section: Resultsmentioning
confidence: 82%
“…Contextual background for radiological review and classification of interval BCs, along with definitions of the categories of interval BCs, have been outlined in the introduction of the paper; methodological issues have been comprehensively explained in our previous review. 1 Table 2 summarises findings from the literature search on radiological surveillance including the methods used to conduct mammographic review; 10 , 13 15 , 18 , 26 , 31 40 the latter substantially influences the distribution of radiological categories and can bias estimated proportions. 1 , 33 , 41 For example, a pilot study examining radiological review methods showed that informed vs. blinded (uninformed) review of interval BC leads to bias in classification whereby informed reviewers (aware they were reviewing mammograms containing interval cases) more frequently classified some interval BCs as positive, compared to reviewers who were unaware they were reading mammograms of interval BCs that had been added into routine screen-reading practice (‘uniformed’ review).…”
Section: Resultsmentioning
confidence: 99%
“…6 ). Patients with interval breast cancer usually present with an average higher histological grade 7,8 , larger tumor size 9 , and more-metastatic local lymphnodes 10 , a higher proportion of estrogen receptor (ER) 8 /progesterone receptor (PR) negativity 11 , a higher frequency of HER2 positivity 8,9 , and are more often triple negative 12 .…”
Section: Introductionmentioning
confidence: 99%
“…4 Therefore, the detection rate of interval cancers is a key component of quality control for the screening programs. The comprehensive multidisciplinary guidelines for quality assurance in (breast?)…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of interval cancers is critical in determining the sensitivity of screening and represents an objective measure of the quality of the screening program, implicating that increased detection of cancers in the program must lead to a lower incidence of interval cancers. 4 Therefore, the detection rate of interval cancers is a key component of quality control for the screening programs. The comprehensive multidisciplinary guidelines for quality assurance in (breast?)…”
Section: Introductionmentioning
confidence: 99%